Pengembangan Media Pembelajaran Berbasis Aplikasi Android Menggunakan Power Point Dan I-Spring Pada Materi Garis Dan Sudut Untuk Siswa SMP Kelas VII - Yoyada Nufninu; Wara Sabon Dominikus; Imelda Hendriani Eku Rimo (Universitas Nusa Cendana, 2021)
This research aims to produce products in the form of learning media based on android applications using Powerpoint and I-Spring on line and angle materials for junior high school students in grade VII that are valid, practical and effective. The method used in this study is the Research and Development (R&D) method with the ADDIE development model consisting of 5 stages, namely analysis, design, development, implementation and evaluation. Data collection techniques and instruments used were interviews, questionnaires and tests. The data analysis technique used is quantitative and qualitative analysis techniques. The results showed that the learning media based on the android application that was developed met the valid, practical and effective eligibility criteria. The results of the media eligibility were obtained from the assessment of material experts with an average of 4.4 and media expert assessments of 4.4 so that they were categorized as